PENGARUH LINGKUNGAN BELAJAR DAN DUKUNGAN ORANGTUA TERHADAP PRESTASI BELAJAR PADA SISWA KELAS X SMK PGRI 3 KEDIRI - Rega, Yohan; Afandi, Tjetjep Yusuf; Prastyaningtyas, Efa Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to detemine the effect of the learning environment parental support  the learning achievemennt  class X studnts majoring in Aconting at SMK PGRI 3 Kediri. This research approach and technique uses quantitative, while the research technique uses causality. The samplle used in  study was 30 students majoring in accounting class X with SPSS software for windows version 23. Data collection method using questionnaires. . Data analysis used clasical asumptiont test, multiplle regresion analysi test, coficient determination test and hypothesis testing. The resultsthe study using SPSS 23 showthat: 1. The learning environment has  efect on learning achievement with a value of (0.001 < 0.05), which means H0 is rejected. 2. Parental support has an effect on learning achievement with a value of (0.001 <0.05) which means H0 is rejected. 3. The learning environment and parental support affect learning achievement simultaneously (0.003 < 0.005), which means H0 is rejected. With a coefficient of determination of 0.059 or 5.9%. So it was concluded that there was an influce the learning environmen and parental support the learning achievement of class X students majoring in Accounting at SMK PGRI 3 Kediri.